Knitting patterns for dummies - Porter, Kristi (Hoboken, NJ : Wiley Pub., 2007)
Demonstrates how to improve a person's knitting skills with line diagrams and step-by-step instructions on over forty patterns and projects, including scarves, cushions, and baby clothes.--
Includes index.
Keywords: Knitting -- Patterns; Knitting -- Patterns